Predictors of Quality of Life Change in Head-and-Neck Cancer Survivors during Concurrent Chemoradiotherapy: A Prospective Study - Ya-Hui Tsan; Shin-Huey Wung; Ming-Wei Lin; Wen-Liang Lo; Ya-Jung Wang (Elsevier, 2021)
Objective: Head-and-neck cancer (HNC) and its treatment impact patients' quality of life (QoL) and survival. The symptom burden of HNC survivors severely affects QoL, while hope serves as an impetus for adjustment that enables survivors to sustain basic QoL. This study investigated the change of QoL, symptom burden, and hope and the predictors of QoL change in HNC survivors from diagnosis to 3 months after concurrent chemoradiotherapy (CCRT) completing. Methods: This was a prospective, correlational study conducted between January 2016 and April 2017 at a medical center in northern Taiwan. Purposive sampling 54 adults newly diagnosed with HNC had completed the first CCRT. The questionnaires of Functional Assessment of Cancer Therapy-HNC Scale, M. D. Anderson Symptom Inventory, and Herth Hope Index were collected. The five measuring times were before CCRT (T1), the 3rd-4th week of CCRT (T2), the last week of CCRT (T3), and 1 month (T4) and 3 months (T5) after the completion of CCRT. Results: The change of QoL first declined and then rose at T2-T5. The change of symptom burden increased initially and then declined at T2-T5. The change of hope remained steady between T1 and T5. The change of symptom burden and hope significantly predicted the change of QOL over time. Conclusions: Clinicians are suggested to assess symptom burden and hope regularly in HNC during their CCRT and, if needed, promptly provide interprofessional care in time. Reducing symptom burden and maintaining a mindful hope could improve QoL in HNC survivors during CCRT.